CATEGORY, TYPE AND MOTIVE OF SWEAR WORDS IN PASA LAUAK, SUNGAI BARAMEH, LUBUK BEGALUNG DISTRICT IN COVID PANDEMI AS LANGUAGE LEARNING - Muthia Damayanti; Edwar Kemal; Wahyudi Rahmat (Curricula : Journal of Teaching and Learning, 2021)
The researcher analyzed the swear word categories, types, and motives, in Pasa Lauak. Data were collected through recording, taking notes, interview and questionnaire techniques. It was analyzed by a referential method. Andersson and Hughes theories were used to analyze the swear word categories and the motives. Pinker theory was to explain the swearing types. The research shows there are 2 forms of swear words i.e. high for 13 % and low for 87 %. The categories are (a) sexual organs, sexual relations 16 %, (b) religion 13 %, (c) excrement 16 %, (d) physically-mentally disabled 12 %, (e) prostitution 3 %, (f) drugs and crime 3 %, (g) skin color 3 %, (h) family member 10 %, (i) age level 3 %, (j) skin disease 3 % , (k) body size 3 %, (l) animal 7 %, and (m) height level 3 %. The swearing types are abusive swearing 39 %, idiomatic swearing) 42 %, emphatic swearing 3 %, chatartic swearing 16 %. The motives are psychology motive 55 %, social motive 32 %, and working condition motive 16 %. It shows that Pasa Lauak community is creative in creating the swear words. Swear words have negative and positive impacts.